Sherwood Anderson's Winesburg, Ohio - McKenzie, Precious, 1975- (Dialogue (Brill Rodopi (Firm)), 2016)
Sherwood Anderson's Winesburg, Ohio, revisits a classic, twentieth-century American text. Scholars from around the world share their intrepretations and shed new light on Anderson's contribution to Modernism and his legacy to later writers. They look closely at gender relations, masculinity, place, the nature of community, and the elusive American Dream.